The 10-nm chromatin fiber and its relationship to interphase chromosome organization. (20th December 2017) - Hansen, Jeffrey C.; Connolly, Mark; McDonald, Charles J.; Pan, Anyu; Pryamkova, Anna; Ray, Kyle; Seidel, Erik; Tamura, Sachiko; Rogge, Ryan; Maeshima, Kazuhiro
Abstract : A chromosome is a single long DNA molecule assembled along its length with nucleosomes and proteins. During interphase, a mammalian chromosome exists as a highly organized supramolecular globule in the nucleus. Here, we discuss new insights into how genomic DNA is packaged and organized within interphase chromosomes. Our emphasis is on the structural principles that underlie chromosome organization, with a particular focus on the intrinsic contributions of the 10-nm chromatin fiber, but not the regular 30-nm fiber. We hypothesize that the hierarchical globular organization of an interphase chromosome is fundamentally established by the self-interacting properties of a 10-nm zig-zag array of nucleosomes, while histone post-translational modifications, histone variants, and chromatin-associated proteins serve to mold generic chromatin domains into specific structural and functional entities.